Effectiveness of Physiotherapy in Patients with Multiple Sclerosis: Evaluating the Efficacy of Physiotherapy in Multiple Sclerosis Patients (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Chronic inflammation, demyelination, gliosis, or neuronal death are hallmarks of multiplesclerosis (MS), an inflammatory disease of CNS. Improvements in motor efficiency on EDSS,functional assessment on IADL Scale, and also the impact of MS on patients' daily lives on MSIS-29were statistically significant after physiotherapy, suggesting a positive change in the patients'functional status. The study's overarching objective is to evaluate physiotherapy's efficacy inmultiple sclerosis.